Discovery and optimization of aspartate aminotransferase 1 inhibitors to target redox balance in pancreatic ductal adenocarcinoma. Issue 16 (1st September 2018) - Anglin, Justin; Zavareh, Reza Beheshti; Sander, Philipp N.; Haldar, Daniel; Mullarky, Edouard; Cantley, Lewis C.; Kimmelman, Alec C.; Lyssiotis, Costas A.; Lairson, Luke L.
Graphical abstract: Highlights: PDAC tumors are dependent on GOT1 for redox homeostasis and sustained proliferation. 4-(1 H -Indol-4-yl)- N -phenylpiperazine-1-carboxamide is a GOT1 inhibitor. Medicinal chemistry-based optimization resulted in the improvement of potency. A tryptamine-based derivative series of GOT1 inhibitors was identified. Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a lethal malignancy that is extremely refractory to the therapeutic approaches that have been evaluated to date. Recently, it has been demonstrated that PDAC tumors are dependent upon a metabolic pathway involving aspartate aminotransferase 1, also known as glutamate-oxaloacetate transaminase 1 (GOT1), for the maintenance of redox homeostasis and sustained proliferation. As such, small molecule inhibitors targeting this metabolic pathway may provide a novel therapeutic approach for the treatment of this devastating disease. To this end, from a high throughput screen of ∼800, 000 molecules, 4-(1 H -indol-4-yl)- N -phenylpiperazine-1-carboxamide was identified as an inhibitor of GOT1. Mouse pharmacokinetic studies revealed that potency, rather than inherent metabolic instability, would limit immediate cell- and rodent xenograft-based experiments aimed at validating this potential cancer metabolism-related target. Medicinal chemistry-based optimization resulted in the identification of multiple derivatives with >10-fold improvements in potency, as well as the identification of a tryptamine-based series of GOT1 inhibitors.